Influence of shoe torsional stiffness on foot and ankle biomechanics during tennis forehand strokes - Martin, C.; Touzard, P.; Horvais, N.; Puchaud, P.; Kulpa, R.; Bideau, B.; Sorel, A. (European Journal of Sport Science, 2023)
Tennis shoe characteristics need to minimise the risk of athletes suffering ankle injuries and improve players` feet performance. This study aims to evaluate the influence of shoe torsional stiffness on running velocity, stance duration, ground reaction forces and ankle biomechanics during two different tennis forehand runs and strokes. Ten right-handed advanced male tennis players performed two specific tennis forehand runs and strokes at maximal effort (a shuttle run with a defensive open stance forehand - SRDF and a lateral jab run with an offensive open stance forehand - JROF) with four different pairs of tennis shoes with different torsional stiffness. A force platform measured ground reaction forces (GRF). A motion capture system recorded the 3D trajectories of markers located on players` anatomical landmarks. The minimum, maximum angle value, and range of motion were computed using inverse kinematics for each rotation axis of the right ankle. Normalised maximal ankle torques were also computed using inverse dynamics. Shoe torsional stiffness had no effect on running velocity, on stance duration and maximal values of GRF. Shoe torsional stiffness influenced forefoot inversion which was significantly higher for the most flexible shoes. For SRDF, the maximal ankle inversion angle was significantly and largely increased for the stiffest shoe. The stiffest shoe may put the ankle at a higher risk of lateral sprains during SRDF while it was not the case during JROF.